Efficacy and safety of weekly paclitaxel with or without ramucirumab as second-line therapy for the treatment of advanced gastric or gastroesophageal junction adenocarcinoma (RAINBOW-Asia): a randomised, multicentre, double-blind, phase 3 trial. (December 2021) - Xu, Rui-Hua; Zhang, Yanqiao; Pan, Hongming; Feng, Jifeng; Zhang, Tao; Liu, Tianshu; Qin, Yanru; Qin, Shukui; Yin, Xianli; Liu, Baorui; Ba, Yi; Yang, Nong; et al.
Summary: Background: In the global phase 3 RAINBOW study, ramucirumab plus paclitaxel significantly improved overall survival compared with placebo plus paclitaxel in patients with advanced gastric or gastro-oesophageal junction (GEJ) adenocarcinoma. RAINBOW-Asia, a bridging study with similar design to RAINBOW, aimed to evaluate the efficacy and safety of ramucirumab plus paclitaxel for advanced gastric or GEJ adenocarcinoma in Asian, predominantly Chinese, patients. Methods: RAINBOW-Asia was a randomised, double-blind, placebo-controlled, phase 3 trial done at 32 centres in China, Malaysia, the Philippines, and Thailand. Adult patients (≥18 years) with metastatic or locally advanced, unresectable gastric or GEJ adenocarcinoma who previously received fluoropyrimidine–platinum-based chemotherapy were randomly assigned with a centralised interactive web response system in a 2:1 ratio to receive ramucirumab 8 mg/kg or placebo intravenously on days 1 and 15 plus paclitaxel 80 mg/m 2 intravenously on days 1, 8, and 15 of every 28-day cycle. Randomisation was stratified by Eastern Cooperative Oncology Group performance status and presence of peritoneal metastases. The co-primary endpoints were progression-free survival and overall survival. Efficacy analyses were done in the intention-to-treat population, and safety analysis included patients who received at least one dose of study treatment. This trial is registered with ClinicalTrials.gov, NCT02898077, and has been completed. Findings: Between March 2, 2017, and June 30, 2020, 440 patients were randomly assigned to receive ramucirumab plus paclitaxel (n=294) or placebo plus paclitaxel (n=146). Median progression-free survival was 4·14 months (95% CI 3·71–4·30) in the ramucirumab plus paclitaxel group compared with 3·15 months (2·83–4·14) in the placebo plus paclitaxel group (hazard ratio [HR] 0·765, 95% CI 0·613–0·955, p=0·0184). Median overall survival was 8·71 months (95% CI 7·98–9·49) in the ramucirumab plus paclitaxel group and 7·92 months (6·31–9·10) in the placebo plus paclitaxel group (HR 0·963, 95% CI 0·771–1·203, p=0·7426). The most common grade 3 or worse treatment-emergent adverse events were decreased neutrophil count (159 [54%] of 293 patients in the ramucirumab plus paclitaxel group vs 56 [39%] of 145 in the placebo plus paclitaxel group), decreased white blood cell count (127 [43%] vs 42 [29%]), anaemia (46 [16%] vs 24 [17%]), hypertension (21 [7%] vs nine [6%]), and febrile neutropenia (18 [6%] vs one [<1%]). Interpretation: These findings, along with the results from RAINBOW, support the use of ramucirumab plus paclitaxel as second-line therapy in a predominantly Chinese population with advanced gastric or GEJ adenocarcinoma. Funding: Eli Lilly and Company, USA. Translation: For the Chinese translation of the abstract see Supplementary Materials section.